A membrane electrode for PEM water electrolysis with a gradient anode catalyst layer
By adopting a gradient design in the anode catalytic layer, the first and second catalytic layers of high EW and low EW values are constructed, and the problem of mass transfer polarization of the anode catalytic layer under high current density is solved, and the effect of high reaction rate and high electrolytic water energy efficiency is achieved.
Patent Information
- Application Number
- CN202411936202.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
AI Technical Summary
The existing anode catalytic layer has mass transfer polarization problems under high current density, resulting in a decrease in reaction rate and a decrease in electrolytic water energy efficiency.
The anode catalytic layer with a gradient design is constructed near the proton exchange membrane side, and the anode first catalytic layer of the high EW perfluorosulfonic acid resin dispersion is constructed near the proton exchange membrane side, and the anode second catalytic layer of the low EW perfluorosulfonic acid resin dispersion is constructed near the gas diffusion layer side, ensuring that high hydration and high gas mass transfer capacity are maintained under high current density.
The gradient-designed anode catalytic layer significantly reduces mass transfer polarization, improves the reaction rate at high current density and the energy efficiency of electrolyzed water.
Smart Images

Figure CN119776867A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water electrolysis, and in particular relates to a membrane electrode for PEM water electrolysis with a gradient anode catalyst layer. Background Art
[0002] Proton exchange membrane (PEM) water electrolysis technology is an efficient method for hydrogen production. It promotes the decomposition of water into hydrogen and oxygen by applying voltage between the anode and cathode. PEM water electrolysis system has the advantages of high energy efficiency and rapid response, and is widely used in fields such as renewable energy storage and hydrogen energy production. Membrane electrode (MEA) is the core component of proton exchange membrane water electrolysis. The membrane electrode is mainly composed of cathode and anode catalyst layers, proton exchange membrane and cathode and anode gas diffusion layers. The catalyst layer of the membrane electrode contains catalysts and ionomers. Ionomers refer to polymers containing exchangeable ion groups that can promote the conductivity of protons in the catalyst layer. The EW value (Equivalent Weight) of the ionomer refers to the mass of the polymer corresponding to each equivalent ion exchange group (such as sulfonic acid group -SO3H), which is usually used to measure the ion exchange capacity of the ionomer. The lower the EW value, the stronger the ion exchange capacity of the ionomer. Existing membrane electrode anode catalyst layer designs usually adopt a uniform structure, that is, the parameters of the catalyst layer such as ionomer concentration, ionomer EW value and catalyst loading are kept relatively uniform throughout the catalyst layer. This design is effective at lower current densities (less than 2 A / cm 2 ) can provide good reaction performance, but at high current density, especially when the current density reaches 3 A / cm 2 When the mass transfer rate is higher than 100 kHz, mass transfer polarization becomes the main performance bottleneck.
[0003] In the mass transfer process of the anode catalyst layer, there are complex material and electron transport mechanisms. Specifically, it includes the transfer of electrons and oxygen and the transfer of water molecules and protons. (1) Transfer of electrons and oxygen: In the anode catalyst layer, the electrochemical reaction takes place at the three-phase interface, water is oxidized to generate oxygen, and electrons are released at the same time. The electrons are transferred through the catalyst particles and eventually transferred to the external circuit along the conductive path of the electrode (such as the electrode material or the connection between the electrode and the external circuit). Oxygen diffuses through the pores of the anode catalyst layer to the gas diffusion layer (PTL) side to prevent oxygen from accumulating in the anode catalyst layer. This diffusion process depends on the pore structure of the anode catalyst layer. As the reaction proceeds, the concentration of oxygen in the anode catalyst layer gradually increases toward the anode PTL side. (2) Transfer of water molecules and protons: Protons migrate to the proton exchange membrane (PEM) side through the proton conductive channel of the ionomer in the anode catalyst layer to maintain the charge balance of the electrolysis reaction. In addition, water molecules in the anode catalyst layer also need to be transferred to the PEM side through the adsorption and diffusion mechanism of the ionomer to support the stability of the proton conductive channel.
[0004] In summary, the mass transfer process of the anode catalyst layer is a complex interaction process between electrons, oxygen, water molecules and protons. The transfer of electrons and oxygen is mainly carried out from the catalyst layer to the gas diffusion layer (PTL) side, while water molecules and protons are transferred from the catalyst layer to the proton exchange membrane (PEM) side. Therefore, factors such as the microstructure of the catalyst layer, the concentration distribution of the ionomer, and the distribution of the catalyst will affect the efficiency of these mass transfer processes, thereby affecting the overall performance of the water electrolysis reaction.
[0005] The uniform design of the existing anode catalyst layer leads to an increase in the rate of oxygen generation at high current density, while the oxygen transmission rate is limited, especially in the area close to the gas diffusion layer (PTL), where the concentration is too high, blocking the mass transfer channel, thus forming a serious mass transfer polarization, limiting the reaction rate, and causing the energy efficiency of water electrolysis to decrease. In addition, the proton conductivity of the existing anode catalyst layer cannot effectively adapt to the demand for proton transmission under high current density. In the area close to the proton exchange membrane (PEM), the proton concentration increases, and proton transmission may be limited, resulting in an increase in voltage, further affecting the overall efficiency of water electrolysis. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a membrane electrode for PEM water electrolysis with a gradient anode catalyst layer. The anode catalyst layer is constructed in a gradient manner. A first anode catalyst layer containing a higher ionomer solid content and a high EW value of the ionomer is constructed on the side close to the proton exchange membrane (PEM) to avoid water shortage in the catalyst layer and ensure high hydration and high proton transfer capacity at high current density. A second anode catalyst layer containing a lower ionomer solid content and a low EW value of the ionomer is constructed on the side close to the gas diffusion layer (PTL) to avoid excessive ionomer content blocking the gas mass transfer channel under excessive hydration, thereby ensuring high electron conductivity and high gas mass transfer capacity at high current density.
[0007] The present invention is specifically achieved through the following technical scheme. According to a membrane electrode for PEM water electrolysis with a gradient anode catalyst layer proposed by the present invention, it includes a proton exchange membrane, and the two sides of the proton exchange membrane are respectively an anode catalyst layer and a cathode catalyst layer, the other side of the anode catalyst layer is an anode gas diffusion layer, and the other side of the cathode catalyst layer is a cathode gas diffusion layer; the anode catalyst layer is a gradient design, specifically, the anode catalyst layer includes a first anode catalyst layer and a second anode catalyst layer, the first anode catalyst layer is located between the proton exchange membrane and the second anode catalyst layer, the EW value of the ionomer in the first anode catalyst layer is higher than the EW value of the ionomer in the second anode catalyst layer, and the percentage of the dry weight of the ionomer in the first anode catalyst layer to the total solid weight of the first anode catalyst layer is higher than the percentage of the dry weight of the ionomer in the second anode catalyst layer to the total solid weight of the second anode catalyst layer.
[0008] Furthermore, the ionomer in the first catalyst layer of the anode is selected to have an EW value of 950-1100 g mmol -1 The perfluorosulfonic acid resin dispersion, specifically, its EW value is 950 g mmol -1 or 980 g mmol -1 or 1000 g mmol -1 or 1100 gmmol -1 The ionomer in the second catalyst layer of the anode is selected to have an EW value of 720~825 g mmol -1 The perfluorosulfonic acid resin dispersion, specifically, its EW value is 720 g mmol -1 or 725 g mmol -1 or 790 g mmol -1 or 825 g mmol -1 .
[0009] Furthermore, the dry weight of the ionomer in the first anode catalyst layer accounts for 15-30 wt.% of the total solid weight of the first anode catalyst layer; the dry weight of the ionomer in the second anode catalyst layer accounts for 5-15 wt.% of the total solid weight of the second anode catalyst layer.
[0010] Furthermore, the catalyst loading amounts of the first anode catalytic layer and the second anode catalytic layer may be the same or different.
[0011] Furthermore, the catalyst of the cathode catalyst layer is a Pt / C catalyst, and the catalyst of the anode catalyst layer is an iridium oxide catalyst; the ionomer in the cathode catalyst layer is a perfluorosulfonic acid resin dispersion, and its EW value is not limited, and the dry weight of the ionomer in the cathode catalyst layer accounts for 15~30 wt.% of the total solid weight of the cathode catalyst layer.
[0012] The aforementioned PEM membrane electrode for water electrolysis having a gradient anode catalyst layer is prepared according to the following method: (1) Preparation of the first anode slurry: Take a certain amount of iridium oxide catalyst in a container, add a certain amount of ultrapure water and isopropanol to the container in turn, where the volume ratio of ultrapure water to isopropanol is 1: (1~10), and then add a certain volume of EW value of 950~1100g mmol -1 The perfluorosulfonic acid resin dispersion is prepared, and the dry weight of the perfluorosulfonic acid resin accounts for 15-30 wt.% of the total solid weight of the first anode slurry. The prepared first anode slurry is ultrasonically dispersed in an ice-water bath for 1-3 h to obtain a final first anode slurry A. (2) Preparation of the second anode slurry: Take a certain amount of iridium oxide catalyst in a container, add a certain amount of ultrapure water and isopropanol to the container in turn, where the volume ratio of ultrapure water to isopropanol is 1: (1~10), and then add a certain volume of EW value of 720~825g mmol -1 The perfluorosulfonic acid resin dispersion is prepared, and the dry weight of the perfluorosulfonic acid resin is controlled to account for 5-15 wt.% of the total solid weight of the anode second slurry. The prepared anode second slurry is ultrasonically dispersed in an ice water bath for 1-3 h to obtain the final anode second slurry B. (3) Preparation of membrane electrode: The pretreated proton exchange membrane is cut into a suitable size and placed on a cathode spraying platform, and the cathode slurry is dispersed to one side of the proton exchange membrane through an ultrasonic spraying device to construct a cathode catalyst layer; the proton exchange membrane sprayed with the cathode catalyst layer is transferred to the anode spraying platform, and the prepared anode first slurry A is dispersed to the other side of the proton exchange membrane through an ultrasonic spraying device to construct anode first catalyst layer, and then the prepared anode second slurry B is dispersed on the anode first catalyst layer through an ultrasonic spraying device to construct anode second catalyst layer. After spraying, a hot pressing process is performed to obtain a PEM membrane electrode for water electrolysis with a gradient anode catalyst layer.
[0013] Furthermore, the EW value of the perfluorosulfonic acid resin dispersion in step (1) is 950 g mmol -1 or 980 g mmol -1 or 1000 g mmol -1 or 1100 g mmol -1 ; The EW value of the perfluorosulfonic acid resin dispersion in step (2) is 720 g mmol -1 or 725 g mmol -1 or 790 g mmol -1 or 825 g mmol -1 .
[0014] Furthermore, the ultrasonic frequency during ultrasonic dispersion in step (1) and step (2) is 10-40 kHz; the hot pressing temperature in step (3) is 80-140°C, the hot pressing pressure is 0.2-3 MPa, and the hot pressing time is 30-150 s.
[0015] Furthermore, the cathode slurry is prepared according to the following method: a certain amount of Pt / C catalyst is taken into a container, and a certain amount of ultrapure water and isopropanol are added to the container in sequence, wherein the volume ratio of ultrapure water to isopropanol is 1: (1~10), and then a certain volume of perfluorosulfonic acid resin dispersion is added to control the dry weight of the perfluorosulfonic acid resin to account for 15~30wt.% of the total solid weight of the cathode slurry, and the prepared cathode slurry is ultrasonically dispersed in an ice water bath for 1~3 h, and the ultrasonic frequency is 10~40 kHz to obtain a final cathode slurry; wherein the Pt content in the Pt / C catalyst is 20~60 wt.%, specifically, the Pt content in the Pt / C catalyst is 20wt.% or 30 wt.% or 40 wt.% or 50 wt.% or 60wt.%.
[0016] Furthermore, in step (3), the Pt loading of the cathode catalyst layer is 0.1-1.0 mg / cm 2 The Ir loading of the first catalyst layer of the anode is 0.2~1.0 mg / cm 2 The Ir loading of the second catalyst layer of the anode is 0.2~1.0 mg / cm 2 .
[0017] Compared with the prior art, the present invention has obvious advantages and beneficial effects. By means of the above technical solution, the present invention can achieve considerable technical progress and practicality, and has a wide range of utilization value, and has at least the following advantages: (1) The present invention adopts a gradient method in the construction of the anode catalyst layer. On the side close to the proton exchange membrane (PEM), the first anode catalyst layer containing a higher ionomer solid content is constructed to avoid water shortage in the catalyst layer and ensure high hydration and high proton transfer capacity at high current density. On the side close to the gas diffusion layer (PTL), the second anode catalyst layer containing a lower ionomer solid content is constructed to avoid excessive ionomer content, which blocks the gas mass transfer channel under excessive hydration, and ensure high electron conductivity and high gas mass transfer capacity at high current density.
[0018] (2) At the same time, the present invention selects a perfluorosulfonic acid resin with a high EW value when constructing the first anode catalytic layer, and selects a perfluorosulfonic acid resin with a low EW value when constructing the second anode catalytic layer. By controlling the balance between the total functional ion exchange group content in the first anode catalytic layer and the second anode catalytic layer, the proton exchange capacity of the entire anode catalytic layer and the continuity of the proton transport channel are effectively controlled, thereby ensuring the optimal balance between the proton conduction capacity and the oxygen mass transfer capacity of the anode catalytic layer in different regions, thereby avoiding uneven performance and reduced reaction efficiency.
[0019] (3) Gradient design refers to the gradient distribution of ionomer concentration, ionomer EW value, catalyst loading, etc. along the thickness of the catalyst layer in the design of the membrane electrode catalyst layer to achieve regional optimization performance. Gradient design helps to reduce mass transfer polarization, thereby significantly improving electrochemical performance at high current density, especially by optimizing proton conductivity and oxygen mass transfer capacity, reducing limiting factors in the mass transfer process, and improving the overall water electrolysis efficiency. Through the comparative test of the present invention, it can be known that the anode catalyst layer adopts a gradient design, and the solid content of the ionomer in the first catalyst layer and the second catalyst layer of the anode is distributed in a gradient (the solid content of the ionomer in the first catalyst layer of the anode is higher than the solid content of the ionomer in the second catalyst layer of the anode), and at the same time, the EW value of the ionomer selected in the first catalyst layer and the second catalyst layer of the anode is distributed in a gradient (the first catalyst layer of the anode selects a perfluorosulfonic acid resin with a high EW value, and the second catalyst layer of the anode selects a perfluorosulfonic acid resin with a relatively low EW value). When both conditions are met, the prepared membrane electrode has the best performance. At high current density, it can accelerate the oxygen transfer rate, while improving the proton conductivity and the mass transfer polarization phenomenon, thereby improving the reaction rate at high current density and the energy efficiency of water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the structure of the membrane electrode prepared in Example 1.
[0021] Figure 2 It is a curve diagram of the change of voltage with current density when the membrane electrode prepared in Example 1 and the membrane electrode prepared in Comparative Example 1 are used for electrolysis of water.
[0022] Figure 3 It is a curve diagram of the change of voltage with current density when the membrane electrode prepared in Example 1 and the membrane electrode prepared in Comparative Example 2 are used for electrolysis of water.
[0023] Figure 4 It is a curve diagram of the change of voltage with current density when different membrane electrodes prepared in Examples 1 to 5 are used for electrolysis of water.
[0024] Figure 1 In the figure, 1-anode gas diffusion layer; 2-anode second catalyst layer; 3-anode first catalyst layer; 4-proton exchange membrane; 5-cathode catalyst layer; 6-cathode gas diffusion layer. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In the following examples, if the specific conditions are not specified, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. The raw materials and reagents used without indicating the manufacturer are all conventional products that can be purchased commercially. The perfluorosulfonic acid resin dispersion used in the following examples is a commercially available product, and its EW value, specific gravity and solid content are known. The dry weight of the perfluorosulfonic acid resin described in the examples is equal to the product of the usage volume of the perfluorosulfonic acid resin dispersion and its specific gravity and solid content. The total weight of the slurry solids is equal to the sum of the mass of the catalyst and the mass of the dry weight of the perfluorosulfonic acid resin.
[0027] Example 1 (1) Proton exchange membrane pretreatment Perfluorosulfonic acid membrane was used as the proton exchange membrane. A 3 wt.% hydrogen peroxide solution was heated to 80°C, and then the proton exchange membrane was placed in it for cleaning for 60 minutes. After completion, the proton exchange membrane was rinsed several times with deionized water. After cleaning, the proton exchange membrane was placed in a 0.5 M sulfuric acid solution heated to 80°C and kept warm for 60 minutes. Then, it was rinsed again with deionized water until neutral, and then placed in deionized water at 80°C and kept warm for 60 minutes. Finally, the proton exchange membrane was rinsed and dried and stored at room temperature.
[0028] (2) Cathode slurry preparation 31.25 mg of commercially available Pt / C catalyst (Pt loading in Pt / C catalyst is 40 wt.%) was weighed into a container, 7.41 mL of ultrapure water and 17.30 mL of isopropanol were added to the container in sequence, and then 291.15 μL of perfluorosulfonic acid resin dispersion was added (the EW value of the perfluorosulfonic acid resin dispersion used in the cathode slurry is not limited, and the EW value of the perfluorosulfonic acid resin dispersion used in the cathode slurry prepared in this embodiment is 1000 g mmol -1 , solid content is 5 wt.%), and the dry weight of perfluorosulfonic acid resin (ionomer) is controlled to account for 30 wt.% of the total solid weight of the cathode slurry. The prepared cathode catalyst slurry is ultrasonically dispersed in an ice-water bath for 1 h to obtain the final cathode slurry.
[0029] (3) Preparation of the first anode slurry Weigh 32.05 mg of commercially available iridium oxide catalyst into a container, add 14.94 mL of ultrapure water and 34.86 mL of isopropanol to the container in sequence, and then add 196.52 μL of a perfluorosulfonic acid resin dispersion with a high EW value (the EW of the perfluorosulfonic acid resin dispersion is 1000 g mmol -1, solid content is 5 wt.%), and the dry weight of the perfluorosulfonic acid resin (ionomer) is controlled to account for 22 wt.% of the total solid weight of the first anode slurry. The prepared first anode slurry is ultrasonically dispersed in an ice-water bath for 1 h to obtain the final first anode slurry A.
[0030] (4) Preparation of anode second slurry Weigh 32.05 mg of commercially available iridium oxide catalyst into a container, add 14.99 mL of ultrapure water and 34.99 mL of isopropanol to the container in sequence, and then add 12.11 μL of a perfluorosulfonic acid resin dispersion with a low EW value (the EW of the perfluorosulfonic acid resin dispersion is 790 g mmol -1 , solid content is 25 wt.%), and the dry weight of the perfluorosulfonic acid resin (ionomer) is controlled to account for 8 wt.% of the total solid weight of the anode second slurry. The prepared anode second slurry is ultrasonically dispersed in an ice water bath for 1 h to obtain the final anode second slurry B. The concentration of iridium in the anode second slurry B is equal to the concentration of iridium in the anode first slurry A.
[0031] (5) Membrane electrode preparation The membrane electrode was prepared by ultrasonic spraying. First, the proton exchange membrane pretreated in step (1) was cut into 5×5 cm 2 , placed on the cathode spraying platform. The cathode slurry prepared in step (2) is dispersed to one side of the proton exchange membrane through ultrasonic spraying equipment to construct the cathode catalyst layer, and the Pt loading of the cathode catalyst layer is controlled to be 0.5 mg / cm 2 The proton exchange membrane sprayed with the cathode catalyst layer was transferred to the anode spraying platform, and the anode first slurry A prepared in step (3) was dispersed to the other side of the proton exchange membrane through ultrasonic spraying equipment to construct the anode first catalyst layer. The Ir loading of the anode first catalyst layer was controlled to be 0.3 mg / cm 2 Then, the anode second slurry B prepared in step (4) is dispersed onto the anode first catalyst layer through ultrasonic spraying equipment to construct the anode second catalyst layer, and the Ir loading of the anode second catalyst layer is controlled to be 0.7 mg / cm 2 Then, a hot pressing process was performed to form the final membrane electrode. During the hot pressing process, the hot pressing temperature was controlled to be 80 °C, the hot pressing pressure was 0.5 MPa, and the hot pressing time was 100 s.
[0032] Example 2 In step (5), the Pt loading of the cathode catalyst layer is controlled to be 0.5 mg / cm 2 , the Ir loading of the first catalyst layer of the anode is controlled to be 0.5 mg / cm 2 , the Ir loading of the second catalyst layer of the anode is controlled to be 0.5 mg / cm 2 The remaining steps and operation procedures are the same as those in Example 1.
[0033] Example 3 (1) Proton exchange membrane pretreatment, same as in Example 1.
[0034] (2) Preparation of cathode slurry, same as in Example 1.
[0035] (3) Preparation of the first anode slurry Weigh 32.05 mg of commercially available iridium oxide catalyst into a container, add 14.98 mL of ultrapure water and 34.96 mL of isopropanol to the container in sequence, and then add 298.61 μL of a perfluorosulfonic acid resin dispersion with a high EW value (the EW of the perfluorosulfonic acid resin dispersion is 1100 g mmol -1 , solid content is 5 wt.%), and the dry weight of the perfluorosulfonic acid resin (ionomer) is controlled to account for 30 wt.% of the total solid weight of the first anode slurry. The prepared first anode slurry is ultrasonically dispersed in an ice-water bath for 1 h to obtain the final first anode slurry.
[0036] (4) Preparation of anode second slurry Weigh 32.05 mg of commercially available iridium oxide catalyst into a container, add 14.99 mL of ultrapure water and 34.98 mL of isopropanol to the container in sequence, and then add 24.59 μL of perfluorosulfonic acid resin dispersion with a low EW value (EW of perfluorosulfonic acid resin dispersion = 720 g mmol -1 , solid content is 25 wt.%), and the dry weight of the perfluorosulfonic acid resin (ionomer) is controlled to account for 15 wt.% of the total solid weight of the anode second slurry. The prepared anode second slurry is ultrasonically dispersed in an ice-water bath for 1 h to obtain the final anode second slurry.
[0037] (5) Membrane electrode preparation The Pt loading of the cathode catalyst layer was controlled to be 0.5 mg / cm 2 , the Ir loading of the first catalyst layer of the anode is controlled to be 0.45 mg / cm 2 , the Ir loading of the second catalyst layer of the anode is controlled to be 0.55 mg / cm 2 The remaining steps and operation procedures are the same as step (5) of Example 1.
[0038] Example 4 (1) Proton exchange membrane pretreatment, same as in Example 1.
[0039] (2) Preparation of cathode slurry, same as in Example 1.
[0040] (3) Preparation of the first anode slurry Weigh 32.05 mg of commercially available iridium oxide catalyst into a container, add 14.94 mL of ultrapure water and 34.86 mL of isopropanol to the container in sequence, and then add 196.52 μL of a perfluorosulfonic acid resin dispersion with a high EW value (the EW of the perfluorosulfonic acid resin dispersion is 1000 g mmol -1 , solid content is 5 wt.%), and the dry weight of the perfluorosulfonic acid resin (ionomer) is controlled to account for 22 wt.% of the total solid weight of the first anode slurry. The prepared first anode slurry is ultrasonically dispersed in an ice-water bath for 1 h to obtain the final first anode slurry.
[0041] (4) Preparation of anode second slurry Weigh 32.05 mg of commercially available iridium oxide catalyst into a container, add 14.98 mL of ultrapure water and 34.96 mL of isopropanol to the container in sequence, and then add 60.59 μL of a perfluorosulfonic acid resin dispersion with a high EW value (the EW of the perfluorosulfonic acid resin dispersion is 1000 g mmol -1 , solid content is 5 wt.%), and the dry weight of the perfluorosulfonic acid resin (ionomer) is controlled to account for 8 wt.% of the total solid weight of the anode second slurry. The prepared anode second slurry is ultrasonically dispersed in an ice-water bath for 1 h to obtain the final anode second slurry.
[0042] (5) Membrane electrode preparation The Pt loading of the cathode catalyst layer was controlled to be 0.5 mg / cm 2 , the Ir loading of the first catalyst layer of the anode is controlled to be 0.3 mg / cm 2 The Ir loading of the second catalyst layer of the anode was controlled to be 0.7 mg / cm 2 The remaining steps and operation procedures are the same as step (5) of Example 1.
[0043] Example 5 (1) Proton exchange membrane pretreatment, same as in Example 1.
[0044] (2) Preparation of cathode slurry, same as in Example 1.
[0045] (3) Preparation of the first anode slurry Weigh 32.05 mg of commercially available iridium oxide catalyst into a container, add 14.99 mL of ultrapure water and 34.97 mL of isopropanol to the container in sequence, and then add 39.30 μL of a perfluorosulfonic acid resin dispersion with a low EW value (the EW of the perfluorosulfonic acid resin dispersion is 790 g mmol -1 , solid content is 25 wt.%), and the dry weight of the perfluorosulfonic acid resin (ionomer) is controlled to account for 22 wt.% of the total solid weight of the first anode slurry. The prepared first anode slurry is ultrasonically dispersed in an ice-water bath for 1 h to obtain the final first anode slurry.
[0046] (4) Preparation of anode second slurry Weigh 32.05 mg of commercially available iridium oxide catalyst into a container, add 14.99 mL of ultrapure water and 34.99 mL of isopropanol to the container in sequence, and then add 12.11 μL of a perfluorosulfonic acid resin dispersion with a low EW value (the EW of the perfluorosulfonic acid resin dispersion is 790 g mmol -1 , solid content is 25 wt.%), and the dry weight of the perfluorosulfonic acid resin (ionomer) is controlled to account for 8 wt.% of the total solid weight of the anode second slurry. The prepared anode second slurry is ultrasonically dispersed in an ice-water bath for 1 h to obtain the final anode second slurry.
[0047] (5) Membrane electrode preparation The Pt loading of the cathode catalyst layer was controlled to be 0.5 mg / cm 2 , the Ir loading of the first catalyst layer of the anode is controlled to be 0.3 mg / cm 2 The Ir loading of the second catalyst layer of the anode was controlled to be 0.7 mg / cm 2 The remaining steps and operation procedures are the same as step (5) of Example 1.
[0048] Comparative Example 1 Steps (1) to (4) are the same as those in Example 1.
[0049] Step (5) Membrane electrode preparation: The membrane electrode is prepared by ultrasonic spraying. First, the pretreated proton exchange membrane is cut into 5×5 cm 2 , placed on the cathode spraying platform. The prepared cathode slurry was dispersed to one side of the proton exchange membrane through ultrasonic spraying equipment to construct the cathode catalyst layer, and the Pt loading of the cathode catalyst layer was controlled to be 0.5 mg / cm 2 The proton exchange membrane sprayed with the cathode catalyst layer was transferred to the anode spraying platform, and only the prepared anode first slurry A was dispersed to the other side of the proton exchange membrane through ultrasonic spraying equipment to construct the anode catalyst layer. The Ir loading of the anode catalyst layer was controlled to be 1 mg / cm 2 Then, a hot pressing process was performed to form the final membrane electrode, and the hot pressing temperature was controlled at 80 °C, the hot pressing pressure was 0.5 MPa, and the hot pressing time was 100 s.
[0050] Comparative Example 2 Steps (1) to (4) are the same as those in Example 1.
[0051] Step (5) Membrane electrode preparation: The membrane electrode is prepared by ultrasonic spraying. First, the pretreated proton exchange membrane is cut into 5×5 cm 2, placed on the cathode spraying platform. The prepared cathode slurry was dispersed to one side of the proton exchange membrane through ultrasonic spraying equipment to construct the cathode catalyst layer, and the Pt loading of the cathode catalyst layer was controlled to be 0.5 mg / cm 2 The proton exchange membrane sprayed with the cathode catalyst layer was transferred to the anode spraying platform, and only the prepared anode second slurry B was dispersed to the other side of the proton exchange membrane through ultrasonic spraying equipment to construct the anode catalyst layer. The Ir loading of the anode catalyst layer was controlled to be 1 mg / cm 2 Then, a hot pressing process was performed to form the final membrane electrode, and the hot pressing temperature was controlled to be 80 °C, the hot pressing pressure was 0.5 MPa, and the hot pressing time was 100 s.
[0052] Figure 1 It is a schematic diagram of the structure of the membrane electrode prepared in Example 1. It can be seen that the anode catalyst layer includes two layers, wherein the first anode catalyst layer is relatively thin, and the second anode catalyst layer is relatively thick.
[0053] Figure 2 The graph is a curve of the change of voltage with current density when the membrane electrode prepared in Example 1 and the membrane electrode prepared in Comparative Example 1 are used for electrolysis of water. It can be seen that at high current density, the voltage of the membrane electrode prepared in Example 1 is significantly lower than the voltage of the membrane electrode prepared in Comparative Example 1.
[0054] Figure 3 The graph is a curve of the change of voltage with current density when the membrane electrode prepared in Example 1 and the membrane electrode prepared in Comparative Example 2 are used for electrolysis of water. It can be seen that at high current density, the voltage of the membrane electrode prepared in Example 1 is significantly lower than the voltage of the membrane electrode prepared in Comparative Example 2.
[0055] Figure 4It is a curve diagram of the voltage variation with current density when the membrane electrodes prepared in Examples 1 to 5 are used for water electrolysis. It can be seen that at high current density, the voltages of the membrane electrodes prepared in Examples 1 to 3 when used for water electrolysis are not much different, while the voltages of the membrane electrodes prepared in Examples 4 to 5 when used for water electrolysis at high current density are significantly higher than the voltages of the membrane electrodes prepared in Examples 1 to 3 when used for water electrolysis at high current density. It is fully demonstrated that when the EW value of the ionomer in the anode catalyst layer and the percentage of the dry weight of the ionomer in the anode catalyst layer to the total weight of the catalyst layer solids both change in a gradient, the obtained membrane electrode has the best performance for water electrolysis at high current density, and the EW value of the anode catalyst layer ionomer close to the proton exchange membrane side and the percentage of the dry weight of the ionomer to the total weight of the catalyst layer solids should be higher than the EW value of the anode catalyst layer ionomer close to the gas diffusion layer side and the percentage of the dry weight of the ionomer to the total weight of the catalyst layer solids. The voltage of the membrane electrode prepared in Example 1 and Example 3 when used for electrolysis of water at high current density is significantly lower than the voltage of the membrane electrode prepared in Example 2 when used for electrolysis of water at high current density, indicating that the performance of the membrane electrode obtained is better when the Ir loading of the first anode catalytic layer and the second anode catalytic layer changes in a gradient, that is, when the thickness of the first anode catalytic layer and the thickness of the second anode catalytic layer change in a gradient.
[0056] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A membrane electrode for PEM water electrolysis with a gradient anode catalyst layer, comprising a proton exchange membrane, with an anode catalyst layer and a cathode catalyst layer on both sides of the proton exchange membrane, characterized in that: The anode catalyst layer includes a first anode catalyst layer and a second anode catalyst layer, wherein the first anode catalyst layer is located between the proton exchange membrane and the second anode catalyst layer, the EW value of the ionomer in the first anode catalyst layer is higher than the EW value of the ionomer in the second anode catalyst layer, and the percentage of the dry weight of the ionomer in the first anode catalyst layer to the total solid weight of the first anode catalyst layer is higher than the percentage of the dry weight of the ionomer in the second anode catalyst layer to the total solid weight of the second anode catalyst layer.
2. The membrane electrode for PEM water electrolysis with a gradient anode catalyst layer as claimed in claim 1, characterized in that: The ionomer in the first catalyst layer of the anode is selected to have an EW value of 950~1100 g mmol -1 The ionomer in the second catalyst layer of the anode is selected to have an EW value of 720~825 g mmol -1 Perfluorosulfonic acid resin dispersion.
3. The membrane electrode for PEM water electrolysis with a gradient anode catalyst layer as claimed in claim 1 or 2, characterized in that: The dry weight of the ionomer in the first anode catalyst layer accounts for 15-30 wt.% of the total solid weight of the first anode catalyst layer; the dry weight of the ionomer in the second anode catalyst layer accounts for 5-15 wt.% of the total solid weight of the second anode catalyst layer.
4. The membrane electrode for PEM water electrolysis with a gradient anode catalyst layer as claimed in claim 1, characterized in that: The catalyst loading amounts of the first anode catalytic layer and the second anode catalytic layer are the same or different.
5. The membrane electrode for PEM water electrolysis with a gradient anode catalyst layer as claimed in claim 1 or 4, characterized in that: The catalyst of the cathode catalyst layer is a Pt / C catalyst, and the catalyst of the anode catalyst layer is an iridium oxide catalyst; the ionomer in the cathode catalyst layer is a perfluorosulfonic acid resin dispersion, and the dry weight of the ionomer in the cathode catalyst layer accounts for 15-30 wt.% of the total solid weight of the cathode catalyst layer.
6. The PEM membrane electrode for water electrolysis with a gradient anode catalyst layer as claimed in claim 1, characterized in that: Prepare as follows: (1) Preparation of the first anode slurry: Take a certain amount of iridium oxide catalyst in a container, add a certain amount of ultrapure water and isopropanol to the container in turn, where the volume ratio of ultrapure water to isopropanol is 1: (1~10), and then add a certain volume of EW value of 950~1100 g mmol -1 The perfluorosulfonic acid resin dispersion is prepared, and the dry weight of the perfluorosulfonic acid resin accounts for 15-30 wt.% of the total solid weight of the first anode slurry. The prepared first anode slurry is ultrasonically dispersed in an ice-water bath for 1-3 h to obtain a final first anode slurry A. (2) Preparation of the second anode slurry: Take a certain amount of iridium oxide catalyst in a container, add a certain amount of ultrapure water and isopropanol to the container in turn, where the volume ratio of ultrapure water to isopropanol is 1: (1~10), and then add a certain volume of EW value of 720~825 g mmol -1 The perfluorosulfonic acid resin dispersion is prepared, and the dry weight of the perfluorosulfonic acid resin is controlled to account for 5-15 wt.% of the total solid weight of the anode second slurry. The prepared anode second slurry is ultrasonically dispersed in an ice water bath for 1-3 h to obtain the final anode second slurry B. (3) Preparation of membrane electrode: The pretreated proton exchange membrane is cut into a suitable size and placed on a cathode spraying platform, and the cathode slurry is dispersed to one side of the proton exchange membrane through an ultrasonic spraying device to construct a cathode catalyst layer; the proton exchange membrane sprayed with the cathode catalyst layer is transferred to the anode spraying platform, and the prepared anode first slurry A is dispersed to the other side of the proton exchange membrane through an ultrasonic spraying device to construct anode first catalyst layer, and then the prepared anode second slurry B is dispersed on the anode first catalyst layer through an ultrasonic spraying device to construct anode second catalyst layer. After spraying, a hot pressing process is performed to obtain a PEM membrane electrode for water electrolysis with a gradient anode catalyst layer.
7. The membrane electrode for PEM water electrolysis with a gradient anode catalyst layer as claimed in claim 6, characterized in that: The EW value of the perfluorosulfonic acid resin dispersion in step (1) is 950 g mmol -1 or 980 g mmol -1 or 1000 g mmol -1 or 1100 g mmol -1 ; The EW value of the perfluorosulfonic acid resin dispersion in step (2) is 720 g mmol -1 or 725 g mmol -1 or 790 g mmol -1 or 825 g mmol -1 .
8. The PEM membrane electrode for water electrolysis having a gradient anode catalyst layer as claimed in claim 6, characterized in that: The ultrasonic frequency during ultrasonic dispersion in step (1) and step (2) is 10-40 kHz; in step (3), the hot pressing temperature is 80-140°C, the hot pressing pressure is 0.2-3 MPa, and the hot pressing time is 30-150 s.
9. The PEM water electrolysis membrane electrode with a gradient anode catalyst layer as claimed in claim 6, characterized in that: The cathode slurry is prepared according to the following method: a certain amount of Pt / C catalyst is placed in a container, and a certain amount of ultrapure water and isopropanol are added to the container in sequence, wherein the volume ratio of ultrapure water to isopropanol is 1: (1-10), and then a certain volume of perfluorosulfonic acid resin dispersion is added, and the dry weight of the perfluorosulfonic acid resin is controlled to account for 15-30 wt.% of the total solid weight of the cathode slurry. The prepared cathode slurry is ultrasonically dispersed in an ice water bath for 1-3 h, and the ultrasonic frequency is 10-40 kHz to obtain the final cathode slurry; wherein the Pt content in the Pt / C catalyst is 20-60 wt.%.
10. The PEM membrane electrode for water electrolysis having a gradient anode catalyst layer as claimed in claim 6, characterized in that: The Pt loading of the cathode catalyst layer in step (3) is 0.1-1.0 mg / cm 2 The Ir loading of the first catalyst layer of the anode is 0.2~1.0 mg / cm 2 The Ir loading of the second catalyst layer of the anode is 0.2~1.0 mg / cm 2 .
Citation Information
Cited By
Membrane electrode with multi-layer gradient structure, and preparation method and application of membrane electrode catalyst layer
CN121460643A